Edukasi Gizi Spesifik Sebagai Gerakan 1000 Hari Pertama Kehidupan (HPK) Dalam Upaya Pencegahan Stunting Balita Pada Siswi di SMK Farmasi Al Furqan Banjarmasin - Khairul Anam; Norfai Norfai; Meilya Farika Indah (Jurnal Abdimas Kesehatan (JAK), 2021)
The purpose of this service is to transform and increase student knowledge about specific nutrition in the First 1000 Days of Life. The counseling method is carried out with two methods, namely the lecture method and the discussion method that uses media of power points. Before starting the counseling, a pretest activity is conducted on "Specific Nutrition in the First 1000 Days of Life", then after being given counseling, the questionnaire is distributed again to be refilled by female students, after knowledge data, before and after counseling has been obtained, then analyzed using the statistical test Paired Sample T test. Based on the results of service activities at Al Furqan Pharmacy Vocational School in Banjarmasin, it shows that the p-value (0,000) <α (0.05) which means that there is a statistically significant difference in knowledge between before and after counseling using power point media, it is concluded that the counseling method uses power point media conducted at the Al Furqan Pharmacy Vocational School in Banjarmasin capable and successfully effectively increasing student knowledge about "Specific Nutrition as a movement the First 1000 Days of Life in Preventing efforts of Stunting in children under five years